Gas sensing properties of MWCNT layers electrochemically decorated with Au and Pd nanoparticles - Dilonardo, Elena; Penza, Michele; Alvisi, Marco; Rossi, Riccardo; Cassano, Gennaro; Di Franco, Cinzia; Palmisano, Francesco; Torsi, Luisa; Cioffi, Nicola (Beilstein Journal of Nanotechnology, 2017)
Multiwalled carbon nanotube (MWCNT)-based chemiresistors were electrochemically decorated with Au and Pd nanoparticles (NPs), resulting in an improvement in the detection of gaseous pollutants as compared to sensors based on pristine MWCNTs. Electrophoresis was used to decorate MWCNTs with preformed Au or Pd NPs, thus preserving their nanometer-sized dimensions and allowing the metal content to be tuned by simply varying the deposition time. The sensing response of unmodified and metal-decorated MWCNTs was evaluated towards different gaseous pollutants (e.g., NO2, H2S, NH3 and C4H10) at a wide range of concentrations in the operating temperature range of 45–200 °C. The gas sensing results were related to the presence, type and loading of metal NPs used in the MWCNT functionalization. Compared to pristine MWCNTs, metal-decorated MWCNTs revealed a higher gas sensitivity, a faster response, a better stability, reversibility and repeatability, and a low detection limit, where all of these sensing properties were controlled by the type and loading of the deposited metal catalytic NPs. Specifically, in the NO2 gas sensing experiments, MWCNTs decorated with the lowest Au content revealed the highest sensitivity at 150 °C, while MWCNTs with the highest Pd loading showed the highest sensitivity when operated at 100 °C. Finally, considering the reported gas sensing results, sensing mechanisms have been proposed, correlating the chemical composition and gas sensing responses.
Keywords: Au nanoparticle; chemiresistive gas sensor; electrophoretic deposition; electrosynthesis; metal-functionalized MWCNTs; Pd nanoparticle